Use your planets wisely eaudiobook Master your ultimate cosmic potential with psychological astrology. - Freed, Jennifer (Tantor Media, 2020)
Transform your life and grow into your highest potential using psychological astrology. "Who am I, really? What did I come here to do? Who am I in relationships?" A good therapist will help you answer these questions; so will a good astrologer. For the last twenty-five years, Dr. Jennifer Freed has combined her deep understanding of both these practices to deeply transform people's lives. Dr. Jennifer Freed introduces you to psychological astrology as a way to dive deep into understanding yourself and others in a profound and life-changing way. If you think of yourself as simply a Virgo or a Pisces or a Capricorn, be prepared to expand your self-knowledge manyfold. The knowledge in this book will give you a far more complete picture of your psychological and emotional blueprint. By understanding your cosmic DNA, nine core strengths, and cosmic committee, you'll come to trust that there is a divine orchestration that guides you, that you have a purpose in the world, and that both your light and your shadows are welcome participants in your psychological and relational lives.